Dos Açores para o Continente : proposta de exposição itinerante de uma coleção privada sobre a indústria baleeira - Segundo, Ana Patrícia Chagas Dias (2019)
This dissertation has for an object of study a private collection never seen before associated to the whaling industry of the Azores, focusing on the Pico Island, property of Master Commander Lizuarte Machado. After the meticulous inventory of the collection, the main goal of this work is to disclose, a theme of absolut relevancy to the cultural history of the Azores, meant to be in realize in the form of an itinerant exhibition intended be presented in museums of continental Portugal whose mission and vocation has for focus the marine theme.In order to allow the concretization of the after mentioned exhibit in museums with the distinctive technical and venue features, two different models were conceived – the minimal and the developed – With a larger or a smaller number of exposed objects, each exhibition model remains true to the main message and the objectives of the exhibition itself: to give the opportunity of knowing one of the main Azorean economical activities, between 1850 and 1985, with relevance until 1950, coinciding with the end of world war II, currently extinct. With this exhibit it’s presented these two models, that contain all the tools necessary for it to be integrated and shown in various museums and entities, offering a full package that it has all the conditions and guidelines necessary for the concretization, disclosure and maintenance necessary for this exhibit. The objects that are part of this collection and that are chosen to be exposed, represent the various themes related with the daily habits of a community that was focused in the whale hunting and to the objects from blacksmiths, farmers, carpenters, weavers, scrimshaw, utensils used in the domestic life and the respective documentation. With this exhibition it’s intended not only the disclosure of a relevant private collection, but and above all, an economic activity and a way of life that is characteristic of a specific community, that remains partially unknown from the Portuguese who inhabit the continent.